Pengaruh Program Airport Educational Tour “Discover YIA” Bandar Udara International Yogyakarta Terhadap Ketertarikan Masyarakat Tentang Kebandarudaraan - Tri Febriantini; Nur Makkie Perdana Kusuma (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Discover YIA program is a commitment of PT Angkasa Pura I (Persero) in providing services and comfort to airport service users, as well as an effort to support information disclosure and education processes regarding local cultural wisdom and Yogyakarta icons at Yogyakarta International Airport. This study aims to determine the influence of the